PERFORATION OF THE URINARY BLADDER WALL BY FOLEY CATHETER - Bozgeyik, Z.; Kocakoc, E.; Aglamis, S.; Ogur, E. (Assoc Royal Soc Scientifiques Medicales Belges, 2013)
[Abstract Not Available]
Keywords: Catheters and catheterization; complications